2020
DOI: 10.1177/0890117120920451
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Mental Health, Well-Being, Physical Health, and Lifestyle Behaviors in Physicians and Nurses: A Systematic Review

Abstract: Objective: This systematic review focused on randomized controlled trials (RCTs) with physicians and nurses that tested interventions designed to improve their mental health, well-being, physical health, and lifestyle behaviors. Data Source: A systematic search of electronic databases from 2008 to May 2018 included PubMed, CINAHL, PsycINFO, SPORTDiscus, and the Cochrane Library. Study Inclusion and Exclusion Criteria: Inclusion criteria included an RCT design, samples of physicians and/or nurses, and publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
181
2
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(202 citation statements)
references
References 45 publications
(186 reference statements)
7
181
2
12
Order By: Relevance
“…20,25,26 Both healthy work environments and clinician self-care are critical factors in delivering safe patient care. 27 Health care system leaders employing nurses are responsible for promoting and sustaining a healthy work environment. The COVID-19 crisis has underscored this basic need.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…20,25,26 Both healthy work environments and clinician self-care are critical factors in delivering safe patient care. 27 Health care system leaders employing nurses are responsible for promoting and sustaining a healthy work environment. The COVID-19 crisis has underscored this basic need.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…However, nurses in this study who reported that their institution provided support for their well-being had better physical and mental health outcomes than those who did not report wellness support. To improve the population health of clinicians to ensure quality health care, it is essential for healthcare leaders to create cultures of wellness and implement evidence-based programs (e.g., anonymous mental health screening, cognitive-behavioral therapy-based skills building and mindfulness programs, and gratitude boards; Melnyk et al, 2020). Problematic system issues, such as poor nurse-patient staffing ratios, prolonged 12-hour shifts, and cumbersome documentation requirements in electronic medical records also must be addressed.…”
Section: Take Care Of Yourself and Your Team To Optimize Health And Wmentioning
confidence: 99%
“…Concerns about these data are compounded by high rates of pre-existing mental health and substance use disorders in this population,5 with physicians having rates of suicide among the highest of any profession 6. Although evidence based effective interventions and treatments are available, barriers such as stigma and lack of time limit their uptake, even in normal times 789. Less is known about interventions for the mental health of healthcare workers during pandemics.…”
mentioning
confidence: 99%